Marketing Optimization Strategy of Cassava-Based MSMEs Through Cluster Development: A SWOT Analysis in Pandansari Lor Village - Luthfil Godriyah; Ugik Romadi; Budianto Budianto (Politeknik Pembangunan Pertanian Manokwari, 2026)
Marketing optimization has an important role in the development of a business, especially for Micro, Small and Medium Enterprises (MSMEs). The gap in this research lies in the minimal use of technology and integrated digital-based marketing strategies in the development of cassava-processed MSMEs, although the potential for collaboration through cluster formation and SWOT analysis shows great opportunities to increase competitiveness and business sustainability. This study aims to find out how to optimize the marketing of processed cassava products through the establishment of cassava clusters in Pandansari Lor Village by combining MSMEs with the same business so that information exchange, both innovation and technology can be quickly delivered. Purposive sampling of 20 MSMEs with criteria such as MSMEs with a duration of less than 5 years and marketing that is still carried out conventionally. The research method used is quantitative and uses SWOT analysis. The results of the study are expected to provide insight into marketing optimization strategies through the formation of clusters and can increase the competitiveness of MSMEs in a wider market. Optimization of marketing of processed cassava products can be done through the creation of packaging designs and promotional content designs as well as through the formation of cassava clusters in MSMEs of processed cassava products in Pandansari Lor Village which is strengthened by a SWOT analysis with an SO (strength - opportunity) value of 4.20, thus indicating that the SO strategy has high potential for sustainable growth and success.